Implication of night work on quality of life (Research, Society and Development, 2021)
Industrial and technological developments culminated in the flexibilization of the workload, updates in biological changes in the circadian cycle of requirements. This study aims to analyze whether nighttime habits related to work activities compromise workers' health. An integrative review carried out through searches in the Portal Regional da Biblioteca Virtual em Saúde (BVS), using the Medline, Lilacs, Ibecs databases, as well as the Pubmed, Google Scholar and ResearchGate platforms. First-class original articles, available in full, and detailed, published between 2004 and 2021, were included. An authorial instrument was used for data extraction in Excel. The protocol of the PICOS strategy was followed. The results obtained revealed that sleepless nights resulted in work performance and increased the risk of accidents in the workplace. Sleep favors weight gain, in addition to negatively affecting mood. In this sense, the quality of life of night shift workers is impaired, with prevalence of alcohol consumption, tobacco use, inadequate eating habits and sedentary lifestyle among these individuals. It is concluded that sleep is important for quality of life in all aspects, whether physical, social, emotional or cognitive.